Household Air Pollution and Risk of Pneumonia in Children Under Five: A Systematic Literature Review from Low- and Middle-Income Countries - Bob Wahyudin; Bayu Pratama Putra; Sukaeni Ibrahim (Universitas Pahlawan Tuanku Tambusai, 2026)
Household air pollution remains a critical environmental determinant of child health in low- and middle-income countries, where reliance on solid fuels for cooking and heating persists. This systematic literature review synthesizes empirical evidence examining the association between household air pollution and pneumonia among children under five years of age. A structured search of the Scopus database identified 569 records, of which eight studies met predefined inclusion criteria following PRISMA-guided screening and eligibility assessment. Included studies comprised cross-sectional analyses, hospital-based observational research, randomized intervention trials, and meta-analyses conducted across diverse geographical settings. Evidence consistently demonstrated a positive association between exposure to solid fuel combustion and increased risk of pneumonia, although magnitude varied according to exposure measurement strategy and contextual factors. Proxy indicators, such as cooking-fuel type, were frequently used as exposure measures, whereas only a few studies incorporated direct pollutant monitoring. Intervention-based findings indicated that partial reductions in emissions from improved cookstoves did not consistently translate into measurable declines in pneumonia incidence. Socioeconomic disparities, housing conditions, cultural practices, and energy access constraints further shaped differential exposure patterns and vulnerability among children. An integrated interpretation of epidemiological data and environmental health theory underscores the importance of comprehensive clean energy transitions, infrastructure improvements, and sustained behavioral adaptation to mitigate the pediatric respiratory disease burden in resource-limited settings.